ANALISIS AKUNTANSI PERTANGGUNGJAWABAN PADA BALAI KARANTINA PERTANIAN KELAS I PALEMBANG - Rodhiah Patutie; Sitti Murniati (Program Studi Akuntansi, Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy Situbondo, 2023)
The implementation of good governance was a manifestation of appreciation for the objectives of public sector organizational mechanisms in order to fulfill the desires of the community to achieve the goals and ideals of the nation. This understanding required the development and implementation of an accountability system that was appropriate, clear, measurable and valid so that the implementation of organizational activities can be carried out effectively, efficiently, free from Corruption and Corruption and can be accounted for. One of the benefits of public sector accountability was as a basis for budgeting. The budget preparation process was essentially the process of defining roles in achieving the goals and implementation of the budget to be achieved. The aim of this research was to analyze accountability accounting at the Palembang Class I Agricultural Quarantine Center. The method that researchers used in this research is descriptive qualitative method. The research resulted show that: 1) the organizational structure had been running well and has carried out its respective main tasks and functions; 2) Performance assessment had been carried out properly through the e-performance application; 3) Budget preparation had been carried out and involves each responsible unit. 4) Not yet implementing the classification of responsible costs in the form of controllable and uncontrollable costs; and 5) Accountability reports had been reported to the leadership periodically.